Geochronology and geochemistry of a newly identified Permian hornblende gabbro suite in Aqishan–Yamansu Belt, eastern Tianshan, NW China: Implications on petrogenesis and tectonic setting. (31st August 2021) - Jiang, Hongjun; Chen, Huayong; Gong, Lin; Zhang, Shuanliang; Chu, Gaobin; Ai, Yumin
Abstract : Permian mafic‐ultramafic intrusions have great significance for understanding the geodynamic evolution of the Late Palaeozoic eastern Tianshan Orogen due to containing important information on the nature of mantle sources, crust–mantle interaction, and magmatic differentiation. Increasingly, more Permian mafic‐ultramafic intrusions are discovered in the Jueluotage belt, especially in the Kangguer ductile shear zone, whereas the mafic‐ultramafic intrusions in the Aqishan–Yamansu belt are ill‐informed. In this study, we provide zircon U–Pb geochronological, geochemical, and Sr–Nd–Pb–Hf isotopic data of a newly identified hornblende gabbro suite at the Shaquanzi Fe–Cu deposit in the Aqishan–Yamansu Belt. Zircon U–Pb dating results indicate that the Shaquanzi hornblende gabbro was emplaced at Early Permian (ca. 274–265 Ma). The rocks are calc‐alkaline and have arc‐like geochemical features, including enrichments in large‐ion lithophile elements (LILEs: Rb, Ba, K, Pb and Sr) and light rare‐earth elements (LREEs: Nb, Ta, Zr, Hf, and Ti), and depletions in high‐field‐strength elements (HFSEs) with markedly negative Nb and Ta anomalies. The rocks also exhibit depleted‐mantle isotopic signatures, with positive bulk‐rock εNd (t) values of +3.34 to +4.44 and positive zircon εHf (t) values of +2.8 − +8.7, which are relatively more enriched than those of coeval mafic‐ultramafic intrusions from the Kangguer ductile shear zone, but similar to those in the Central Tianshan Massif. We suggest that the Shaquanzi mafic intrusion suite was generated by 10–30% partial melting of a depleted‐mantle source at over 85 km depth, corresponding to the garnet to garnet‐spinel stability field. And the mantle source had likely been metasomatized by slab‐derived fluids of previous subduction. Integrating with geochemical data of the coeval mafic‐ultramafic and felsic intrusive rocks in the adjacent tectonic belts of eastern Tianshan Orogen, we speculate that the Shaquanzi mafic intrusion was formed in a post‐collision extensional setting, probably triggered by slab breakoff. Metasomatism of the depleted lithospheric mantle had likely occurred during the pre‐Permian subduction of the Kangguer oceanic slab. Abstract : The Aqishan–Yamansu belt was under a post‐collisional setting in the latest Carboniferous to Early Permian. The newly identified Permian hornblende gabbro suite in Aqishan–Yamansu Belt is probably the product of extensional‐related mafic magmatism (triggered by post‐collisional slab breakoff), similar to the generation of mafic‐ultramafic intrusions in the Middle Tianshan Massif.